2014
DOI: 10.1155/2014/565291
|View full text |Cite
|
Sign up to set email alerts
|

An Historical Perspective on How Advances in Microscopic Imaging Contributed to Understanding theLeishmaniaSpp. andTrypanosoma cruziHost-Parasite Relationship

Abstract: The literature has identified complex aspects of intracellular host-parasite relationships, which require systematic, nonreductionist approaches and spatial/temporal information. Increasing and integrating temporal and spatial dimensions in host cell imaging have contributed to elucidating several conceptual gaps in the biology of intracellular parasites. To access and investigate complex and emergent dynamic events, it is mandatory to follow them in the context of living cells and organs, constructing scienti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 101 publications
(126 reference statements)
0
8
0
Order By: Relevance
“…In the case of parasites, green fluorescent protein (GFP) originally purified from the jellyfish ( Aequoria victoria ) has been successfully expressed in several protozoan intracellular parasites such as Leishmania species [1012], Trypanosoma [1314], Enatomoeba [15], Plasmodium [16] and Toxoplasma [17], and more recently as a dual combination with other fluorescent reporters (for example with mCherry) to follow the developmental stages of T. gondii [18]. FPs have been also successfully used for deciphering pathogenesis of bacterial intracellular infection (some examples are given in [1924]).…”
Section: Use Of External and Internal Fluorescent Reporters For Inmentioning
confidence: 99%
“…In the case of parasites, green fluorescent protein (GFP) originally purified from the jellyfish ( Aequoria victoria ) has been successfully expressed in several protozoan intracellular parasites such as Leishmania species [1012], Trypanosoma [1314], Enatomoeba [15], Plasmodium [16] and Toxoplasma [17], and more recently as a dual combination with other fluorescent reporters (for example with mCherry) to follow the developmental stages of T. gondii [18]. FPs have been also successfully used for deciphering pathogenesis of bacterial intracellular infection (some examples are given in [1924]).…”
Section: Use Of External and Internal Fluorescent Reporters For Inmentioning
confidence: 99%
“…Since the discovery of Chagas' disease in 1909 (Chagas, ), major leaps in Trypanosoma cruzi biology have been achieved and have resulted in gradually improving advanced techniques for direct parasite observation (Florentino et al , ). Optical and electron microscopy (De Souza, ) are the most commonly used advanced techniques.…”
Section: Introductionmentioning
confidence: 99%
“…However, the steps of the intracellular life cycle in mammalian hosts that involve the obligatory egress of Leishmania amastigote forms from host cells in order to the spread to new host cells and other tissues (tropism) and organisms are likely the least known aspect of the biology of this parasitic protozoan. A search of the early literature revealed that authors emphasized a 'lytic' cycle for this parasite, mainly based on histopathological observations fragmented in space and time (Theodorides, 1997;Dedet, 2007;Florentino et al, 2014). The preferential, almost exclusive, presence of oval-shaped parasites inside macrophages was the most puzzling aspect of leishmaniasis for the first histopathologists who studied the organism (Wright, 1903;Christophers, 1904), highlighting the uniqueness of Leishmania cell infection and supporting a concept of a specialized parasite, with a limited repertoire of cells able to host them.…”
Section: Introductionmentioning
confidence: 99%